(untitled) (Annals of Medical Research, 2021)
Aim: In this study, our aim was to understand and discuss the underlying reason for the development of squamous cell carcinoma (SCC) in patients recieving hydroxyurea and present a case, in whomwe operated to excise the tumoral masses and reconstruct them.